2008
DOI: 10.1248/bpb.31.2265
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Photodynamic Effect Relationships of 24 Glycoconjugated Photosensitizers in HeLa Cells

Abstract: Photodynamic therapy (PDT) with a photosensitizing dye and light irradiation is used to treat cancer; the photosensitizer accumulated in malignant cells photochemically generates highly cytotoxic reactive oxygen species (ROS), such as singlet oxygen ( 1 O 2 ) and hydroxyl radical (OH · ). 1-6) These ROSs damage the microorganella, such as mitochondria, lysosomes, plasma membrane, Golgi apparatus and endoplasmic reticulum, leading to necrotic and/or apoptotic cell death. Because the efficacy of PDT treatment cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
0
25
0
3
Order By: Relevance
“…This approach was utilized in developing 2-[ 18 F]fluoro-2-deoxy-D-glucose for tumor diagnostics using positron emission tomography (PET) as cancer cells tend to show enhanced D-glucose uptake. Yano et al systematically synthesized forty 5, 10, 15, 20-tetraphenylporphyrin (TPP) and chlorine (TPC) derivatives having O-glycoside [34][35][36][37][38]. O-glycosylated TPPs and TPCs have numerous advantages, such as significant reduction of the dark cytotoxicity, improved water-solubility, greater cellular uptake, and sugar-dependent photocytotoxicity [34][35][36][37][38].…”
Section: Implovement Of Photosensitizers By the Conjugation With Biommentioning
confidence: 99%
“…This approach was utilized in developing 2-[ 18 F]fluoro-2-deoxy-D-glucose for tumor diagnostics using positron emission tomography (PET) as cancer cells tend to show enhanced D-glucose uptake. Yano et al systematically synthesized forty 5, 10, 15, 20-tetraphenylporphyrin (TPP) and chlorine (TPC) derivatives having O-glycoside [34][35][36][37][38]. O-glycosylated TPPs and TPCs have numerous advantages, such as significant reduction of the dark cytotoxicity, improved water-solubility, greater cellular uptake, and sugar-dependent photocytotoxicity [34][35][36][37][38].…”
Section: Implovement Of Photosensitizers By the Conjugation With Biommentioning
confidence: 99%
“…No significant difference in Log P was observed, but chlorins 540a and 540c were only slightly more hydrophilic than 540b,d [271] . Similar methods were used by Hirohara et al to study a range of O-glycosylated tetraarylporphyrins and -chlorins, which showed several advantages including reduced dark cytotoxicity, improved water-solubility, better cellular uptake, and sugar-dependent photocytotoxicity [165,261,262,272,273] . The O-glycosylated chlorins had promising photocytotoxicity in HeLa cells but were difficult to purify.…”
Section: 3-dipolar Cycloadditionsmentioning
confidence: 99%
“…cellular uptake and ROS) and structural diversity of the sugar unit [273] . The photocytotoxicity profiles poorly related to the amount of cellular uptake of the PSs.…”
Section: Hydroporphyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…78 The O-glycosylated chlorins had promising photocytotoxicity in HeLa cells but were difficult to purify. 79,80 Photosensitizers 80a, 82, 83, 85, 87 and 88 showed no significant photocytotoxicity at a concentration of 0.5 μM (24 h, 16 J.cm -2 ), while the deprotected photosensitizers 74, 75, 84 and 86 were photocytotoxic (Fig. 17).…”
mentioning
confidence: 97%